Effectiveness of a Nurse-Led Educational Programme on Telemedicine Knowledge among Nursing Students in Dhaka - Chadayan, Chinna; Sweety, Melba Sahaya (Fakultas Kesehatan, Universitas Nurul Jadid, 2025)
ABSTRACTBackground: Telemedicine is transforming healthcare delivery, especially in underserved regions, by increasing access to care. Nursing students' knowledge of telemedicine is essential for preparing them for the evolving healthcare landscape.Objective: This study aimed to assess the effectiveness of a nurse-led educational program in enhancing nursing students' knowledge of telemedicine in Dhaka, Bangladesh.Methods: A quasi-experimental pre-test and post-test design was used with 40 nursing students who had no prior formal education in telemedicine. The intervention consisted of a 2-hour interactive session covering key concepts of telemedicine. Knowledge levels were measured using pre-test and post-test questionnaires. Data analysis involved paired t-tests to evaluate knowledge improvements.Results: Pre-test findings showed 67.5% of students had poor knowledge of telemedicine. After the intervention, 57.5% of students scored in the